2021
DOI: 10.1097/pec.0000000000002532
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Point-of-Care Ultrasound for Diagnosing Hypertrophic Pyloric Stenosis in the Emergency Department

Abstract: Objectives: This study aimed to investigate the feasibility of point-ofcare ultrasound (POCUS) for diagnosing hypertrophic pyloric stenosis (HPS) in the emergency department (ED).Methods: A retrospective study was conducted in infants aged younger than 90 days who were brought to the ED due to vomiting between January 2015 and December 2019. Of these, infants who were clinically suspected of having HPS and underwent ultrasound were included and categorized into 3 groups: POCUS only, POCUS followed by radiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Most studies were recent (published in the last 10 years) as the availability of portable ultrasound machines was not common before the 2010's, when radiologists used to be responsible for ultrasounding patients. POCUS has been shown to decrease the time to diagnosis and treatment ( 12 ). Overall, the gastric POCUS learning curve is short, and several studies showed good reliability of measurements and interpretations ( 7 9 , 12 , 52 , 64 , 69 , 70 , 72 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies were recent (published in the last 10 years) as the availability of portable ultrasound machines was not common before the 2010's, when radiologists used to be responsible for ultrasounding patients. POCUS has been shown to decrease the time to diagnosis and treatment ( 12 ). Overall, the gastric POCUS learning curve is short, and several studies showed good reliability of measurements and interpretations ( 7 9 , 12 , 52 , 64 , 69 , 70 , 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Totally, eight studies were identified ( Table 4 ) ( 5 , 12 , 67 , 69 72 , 80 ), and 652 infants younger than 6 months presenting with signs of HPS were recruited in the ED; three studies examined gastric POCUS performed by surgeons ( 5 , 67 , 69 ) and five by ED physicians ( 12 , 70 72 , 80 ). In these studies, POCUS was compared to RADUS; in four other studies, the learning curve and training were assessed (surgeons training surgeons, surgeons training ED physicians, or ED physicians training ED physicians) ( 69 , 71 , 72 ).…”
Section: Hypertrophic Pyloric Stenosis (Hps)mentioning
confidence: 99%
See 3 more Smart Citations